Handbook of Accounting, Accountability and Governance. Carnegie, Garry D. & Napier, Christopher J. Research Handbooks on Accounting series. Edward Elgar Publishing, UK & USA, 2023 - Gibson, Kathy (De Computis, Revista Española de Historia de la Contabilidad., 2024)
This handbook is distinguished by its focus on the interplay and interconnections between accounting, accountability and governance, and its emphasis on the social and moral, rather than technical, practices enhance its relevance to a range of disciplines. It provides an invaluable resource both for established researchers and senior and graduate students, and the introductory chapter provides a clear ‘roadmap’ enabling easy navigation of areas of interest.